MODERASI SANTRI DALAM PERSFEKTIF SOSIOLOGI PENGETAHUAN: Studi Analisis Pola Kepimipinan Gender dari Habib Saggaf bin Mahdi bin Syekh Abu Bakar bin Salim di Pesantren Al- Ashriyya Nurul Iman Parung-Bogor - Sadari, Sadari (Asosiasi Dosen PTKIS Indonesia, 2021)
Moderation of students in the midst of global developments is a challenge in itself. This of course really depends on the pattern of gender leadership in Islamic boarding schools. This article conducts an in-depth analysis of how the sociology of knowledge can detect the students who have been fostered in Islamic boarding schools, so that in the future they can provide enlightenment to themselves, their families, the people and the nation, so that they become social agents who are able to bring about social change that puts forward an understanding of Islam that is moderate. Moderate means here, of course, to avoid all forms of discrimination that cover socio-cultural aspects to religion. The practice in the discussion here focuses on gender issues in the Gender leadership pattern of Habib Saggaf bin Mahdi bin Sheikh Abu Bakar bin Salim at the Al- Ashriyya Nurul Iman Islamic Boarding School Parung-Bogor. Pesantren in recent times has given a new face to Islamic studies, because the face of pesantren has received a stereotype (negative labeling) for its teachings related to fiqh which always discriminates against women (gender bias). Islam always protects the human rights of both men and women wherever they are, to be able to take part constructively in society. Likewise, Islam guarantees equality and equality of rights in terms of education, health, economy, legal protection, and political rights that enable them to lead and be led or vote and be elected. Through the sociology of knowledge, it is known that the role of Pondok Pesantren with its leadership pattern is a vital elan of santri in all the movements of their lives in the future. This article explains how to look at these two components.